1994
DOI: 10.1017/s0033291700026969
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cognitive recovery following withdrawal from long-term benzodiazepine use

Abstract: SynopsisTwenty-one patients with significant long-term therapeutic benzodiazepine (BZ) use, who remained abstinent at 6 months follow-up after successfully completing a standardized inpatient BZ withdrawal regime, and 21 normal controls matched for age and IQ but not for anxiety, were repeatedly tested on a simple battery of routine psychometric tests of cognitive function, pre- and post-withdrawal and at 6 months follow-up. The results demonstrated significant impairment in patients in verbal learning and mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 24 publications
(30 reference statements)
1
43
0
3
Order By: Relevance
“…In our study, both lorazepam and placebo participants benefited from the second repetition. The observed improvement of memory after repetition of the items may be of clinical relevance, as cognitive-function experiments on the longterm effects of benzodiazepines suggest that tolerance to the memory deficits caused by benzodiazepines never fully develops (Gorenstein et al, 1995;Tata et al, 1994). Another observation that may be useful for the cognitive remediation was a difference in the reported use of strategy: most of the placebo participants reported using mental imagery with visualization of the associated words.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, both lorazepam and placebo participants benefited from the second repetition. The observed improvement of memory after repetition of the items may be of clinical relevance, as cognitive-function experiments on the longterm effects of benzodiazepines suggest that tolerance to the memory deficits caused by benzodiazepines never fully develops (Gorenstein et al, 1995;Tata et al, 1994). Another observation that may be useful for the cognitive remediation was a difference in the reported use of strategy: most of the placebo participants reported using mental imagery with visualization of the associated words.…”
Section: Discussionmentioning
confidence: 95%
“…5 years later (Kilic¸et al 1999). Tata et al (1994) found little improvement in episodic memory function 6 months after 21 patients had withdrawn from high (mean 42 mg diazepam) doses. Thus, there may be a differential profile of recovery following BZD withdrawal on episodic memory, working memory and other cognitive processes.…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…There are several plausible mechanisms through which that might occur. For example, benzodiazepines have been found to interfere in a dose-dependent way with both acquisition and retention of new information (23)(24)(25), although partial tolerance to those effects has been reported to occur with repeated dosing (26). To the extent that learning is impaired by benzodiazepines, the ability of patients to benefit fully from concurrent psychotherapy may be compromised.…”
Section: Benzodiazepine Therapymentioning
confidence: 99%